Endogenous endophthalmitis secondary to Burkholderia cepacia: A rare presentation - Kurumkattil, Raji (Indian J Ophthalmol, 2020)
Burkholderia cepacia (previously known as Pseudomonas cepacia) is low virulent, gram negative bacilli, known to cause infections in immunocompromised hosts. There are reports about this organism causing keratitis, acute or delayed postoperative, or post traumatic endophthalmitis. Persistence of infection and poor visual outcome are well known complications of infection caused by this organism. Endogenous endophthalmitis due to Burkholderia cepacia is rare. There is no such case report available of endogenous endophthalmitis caused by these bacteria in the literature, where it is presented as retinal abscess and retinal vasculitis. Our aim is to report such a rare case from our hospital, which was treated with systemic and intravitreal antibiotics, with control of infection.